Analisis Bibliometrik: Penelitian Game-Based Learning pada Sekolah Menengah 2005-2023 - Muhammad, Ilham; Triansyah, Fadli Agus; Fahri, Ardian; Gunawan, Ashari (Jurnal Simki Pedagogia, 2023)
Game based learning is game-based learning that involves games in the educational process, aiming to increase learning activities. The purpose of this study is to capture research landscapes related to game-based learning in high school learning from 2005 to 2023. The method used is bibliometric analysis. The database used in collecting the necessary related information is from the Scopus database. Game based learning research publications in secondary schools from 2005 to 2023 have experienced an increase in recent years. The highest number of citations was in 2013. The United States of America is the most influential country in this field. The focus of research related to Game based learning in secondary schools is, 1) computational thinking and understanding; 2) science, technology and development; 3) experience and environment. New themes related to Game based learning research in secondary schools are self-efficacy, computational creativity, inquiry, ar technology and mathematical problems.